Does Prevailing Natural Resource Pool Nearby Matter? A Case Study on Determinants of Participation on Yarshagumba Collection in Dolpa, Nepal - Thapa, Resham B.; Neupane, Sushil (Economic Journal of Nepal, 2008)
This research work explores the socio-economic status of the local peeople, their perception regarding existing scenario of yarshagumba business in local level and factors determining their participation in Yarshagumba collection in Dolpa district using logit model. The findings of the study suggest that there is a considerable variation in people of Dunaj and Juphal intenns of their socio-economic attributes. Income level, sex, literacy and religion had more roles to play with respect to their participation in Yarshagumba collection in coznparisiion to their ethnicity, marital status, language and sickness in the family. The research also identified the prevalance of resource conflict between people and local government bodies regarding property rights and royalty of Yarshagumba collection. In addition. Yarshagumba collection has posed many challenges for conservation programs because of thousands entering into protected regions for the collection activities. Yarshagunzba collection has been emerging as an important source of livelihood to many Nepali people.Key words: Natural resourcse; Economic status; Yarshagumba; Dolpa; NepalEconomic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 31, No. 4 October-December 2008, Issue No. 124Page: 222-234Uploaded date: 5 July 2011